Synthesis, physical properties, and self-assembly of a novel asymmetric aroyleneimidazophenazine - Zhao, Jianfeng (2013)
The synthesis, physical properties, and self-assembly of a novel asymmetric aroyleneimidazophenazine (IZ1) is reported. The as-prepared IZ1 nanowires display an obvious red fluorescence. A heterojunction light-emitting diode (LED) device with the structure ITO/IZ1 nanowires/p-SiC/Al (10 nm)/Ti (80 nm)/Al (380 nm)/ITO was fabricated, and electroluminescence emission with two peaks at about 412 nm and 613 nm was detected with a forward bias ranging from 5 to 10 V.